2014
DOI: 10.1155/2014/803690
|View full text |Cite
|
Sign up to set email alerts
|

Prehypertension and Hypertension among Schoolchildren in Brazzaville, Congo

Abstract: Background. To determine the prevalence and associated factors of prehypertension (pre-HT) and hypertension (HT) in schoolchildren at Brazzaville (Congo). Methods. This cross-sectional study was conducted from March to May 2011 in five representative urban schools in Brazzaville. American Pediatric Society's definition of pre-HT and HT was used. The measurement of blood pressure was obtained using auscultator method. Univariable and multivariable analyses were performed to establish associations between blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
15
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 25 publications
9
15
2
Order By: Relevance
“…The prevalence of hypertension and pre-hypertension in our study was very high but comparable to results obtained by Kemp et al (19), indicating that South African children may have a greater susceptibility to overweight/ obesity associated raised blood pressure which may persist into adulthood (42). Results from other developing countries (43,44) have indicated modest increases in the prevalence of hypertension and pre-hypertension compared to the alarmingly high rates noted in the South African adolescent populations.…”
Section: Correlations Between Msbp/mdbp With Wc Hc and Whtrsupporting
confidence: 87%
“…The prevalence of hypertension and pre-hypertension in our study was very high but comparable to results obtained by Kemp et al (19), indicating that South African children may have a greater susceptibility to overweight/ obesity associated raised blood pressure which may persist into adulthood (42). Results from other developing countries (43,44) have indicated modest increases in the prevalence of hypertension and pre-hypertension compared to the alarmingly high rates noted in the South African adolescent populations.…”
Section: Correlations Between Msbp/mdbp With Wc Hc and Whtrsupporting
confidence: 87%
“…A study conducted by Bertrand Fikahemetal among Brazzivile, Congo students also reported high prevalence of Pre-Hypertension 20.7% and 10 % hypertension. 10 Similar to our study Satyanarayanaetal of Hyderabad found 11.5% PreHypertension and 9.7% hypertension respectively among the same age group. 11 School students of Shimla were found to have 14.3% Pre-hypertension and 4.3% hypertension respectively by Avinashsharmaetal .…”
Section: Discussionsupporting
confidence: 88%
“…In all of these, higher adiposity was associated with higher BP or odds of hypertension. This association was observed in cross‐sectional studies ( n = 46) , and also in prospective studies ( n = 9) . Results were mostly consistent across study type (i.e.…”
Section: Resultssupporting
confidence: 60%